What Next? The Next Transit from Biology to Diagnostics: Next Generation Sequencing for Immunogenetics - Gabriel, Christian (S. Karger GmbH, 2011)
The human genome project triggered the introduction of next generation sequencing (NGS) systems. Although originally developed for total genome sequencing, metagenomics and plant genetics, the ultra-deep sequencing feature of NGS was utilized for diagnostic purposes in HIV resistance and tropism as well in detecting new mutations and tumor clones in oncology. Recent publications exploited the feature of clonal sequencing for immunogenetics to dissolve the growing number of ambiguities. This concept is quite reliable if all exons of interest are tested and the amplification region includes flanking introns. Challenging questions on quality control, cost effectiveness, workflow, and management of enormous loads of data remain if NGS is considered as routine method in the immunogenetics laboratory. If solved, NGS has big potential to have a major impact on immunogenetics by way of providing ambiguity-free HLA-typing results faster, but will also have a great influence on how immunogenetics testing and workflows are organized.